1988
DOI: 10.1136/jnnp.51.3.385
|View full text |Cite
|
Sign up to set email alerts
|

Familial olivopontocerebellar atrophy with neonatal onset: a recessively inherited syndrome with systemic and biochemical abnormalities.

Abstract: SUMMARY Clinical and pathological findings are reported in two siblings who presented in the neonatal period with failure to thrive, hypotonia, pericardial effusions, limitation of joint movement, retinal dystrophy and loss of visual function. Additional features were biochemical evidence of purine overproduction and liver dysfunction. Post mortem, the neuropathological findings in both children were typical of olivopontocerebellar atrophy. It is suggested that the cases represent a recessively inherited inbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 14 publications
1
20
1
1
Order By: Relevance
“…There is debate as to whether these diseases represent an acquired loss of neural tissue or are the result of a primary failure of normal embryological development of the affected structures. Although there has been a case report of OPCH in an infant with in utero phenytoin exposure (Gadisseux et al, 1984) most cases have been postulated to be hereditary (Colan et al, 1981;Lutz et al, 1989;Albrecht et al, 1993;Harding et al, 1988;Kristiansson et al, 1989;Horslen et al, 1991;Chang et al, 1993;Bawle et al, 1995). In our patient, no history of any potential teratogens could be elicited and she did not have any systemic medical disease.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…There is debate as to whether these diseases represent an acquired loss of neural tissue or are the result of a primary failure of normal embryological development of the affected structures. Although there has been a case report of OPCH in an infant with in utero phenytoin exposure (Gadisseux et al, 1984) most cases have been postulated to be hereditary (Colan et al, 1981;Lutz et al, 1989;Albrecht et al, 1993;Harding et al, 1988;Kristiansson et al, 1989;Horslen et al, 1991;Chang et al, 1993;Bawle et al, 1995). In our patient, no history of any potential teratogens could be elicited and she did not have any systemic medical disease.…”
Section: Discussioncontrasting
confidence: 45%
“…These infants present with failure to thrive, generalized hypotonia, areflexia, liver dysfunction, poor sucking reflex, feeding difficulties and dysmorphic features. This disease demonstrates an autosomal recessive pattern of inheritance (Harding et al, 1988;Kristiansson et al, 1989;Horslen et al, 1991;Chang et al, 1993;Bawle et al, 1995) and the diagnosis is confirmed by demonstrating abnormal glycosylation of serum glycoproteins by serum electrophoresis. We did not test for CDGI since the clinical presentations of these two siblings were not consistent with this diagnosis.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Olivopontocerebellar atrophy of neonatal onset, a multisystem disorder with very characteristic neuropathology, was described by Agamanolis et al in 1986 andHarding et at in 1988. Recently we were able to show that, as predicted by Jaeken (1989), this disorder is associated with carbohydrate-deficient gtycoproteins and thus represents the most severe end of the spectrum of diseases recently reviewed by Jaecken et al (1991).…”
Section: Discussionmentioning
confidence: 88%
“…Abnormal oculomotor function (strabismus, nystagmus, oculomotor apraxia) was commonly observed in patients surviving beyond infancy. Additional organ involvement such as gonadal dysgenesis, 16 also seen in patient 23-2 (table e-2 8 ), retinal degeneration or optic nerve atrophy, 5 hepatic fibrosis, and cystic kidney disease 17 are also not yet reported in patients with EXOSC3 mutations. Mesangiocapillary glomeronephritis was diagnosed in a mutation-positive Australian patient 6 (patient 4 in reference 18).…”
Section: How Mutations Inmentioning
confidence: 95%